117. Phrenic nerve palsy in pediatric heart surgery: The neurophysiological contribution in follow up and decision making. Issue 4 (April 2016) - Segatti, A.; Alessandrini, L.; Zanelli, S.; Santuz, P.A.; Biban, P.; Luciani, G.B.; Squintani, G.; Donato, F.; Romito, S.
Abstract : Phrenic nerve palsy after cardiac surgery in infants is a known adverse event. The resulting diaphragmatic dysfunction can lead to ventilatory support weaning failure and other respiratory complications. Diaphragmatic palsy can be resolved with plication, but the timing of the procedure is still debated. The aims of this study were to demonstrate the possibility of a temporary phrenic nerve paralysis, longer than reported in other works, and to compare ultrasounds and electroneurographic findings. 28 infants under one year of age, with different heart malformations, were studied both by phrenic nerve conduction study (pnNCV) and by diaphragmatic ultrasonography, before heart surgery and periodically in the first 4 postoperative months. 11 subjects showed postsurgical phrenic nerve palsy, 5 of which were permanent, with electrophysiological demonstration of prolongation of diaphragmatic action potential (DAP) latency and/or fall in DAP amplitude. A consensual diaphragmatic hypomotility or immobility was found echographically. A correlation seemed to be found between the amplitude of the DAP and both muscular motility at ultrasound and ventilatory dysfunction. We found that both neurophysiology and echography represent important tools in the respiratory follow-up after heart surgery in children, and considerations regarding the timing of the possible recovery of a phrenic neuropathy are discussed.